From birth to death: The hardworking life of Paneth cell in the small intestine - Cui, Chenbin; Wang, Fangke; Zheng, Yao; Wei, Hongkui; Peng, Jian (Frontiers in Immunology, 2023)
Paneth cells are a group of unique intestinal epithelial cells, and they play an important role in host-microbiota interactions. At the origin of Paneth cell life, several pathways such as Wnt, Notch, and BMP signaling, affect the differentiation of Paneth cells. After lineage commitment, Paneth cells migrate downward and reside in the base of crypts, and they possess abundant granules in their apical cytoplasm. These granules contain some important substances such as antimicrobial peptides and growth factors. Antimicrobial peptides can regulate the composition of microbiota and defend against mucosal penetration by commensal and pathogenic bacteria to protect the intestinal epithelia. The growth factors derived from Paneth cells contribute to the maintenance of the normal functions of intestinal stem cells. The presence of Paneth cells ensures the sterile environment and clearance of apoptotic cells from crypts to maintain the intestinal homeostasis. At the end of their lives, Paneth cells experience different types of programmed cell death such as apoptosis and necroptosis. During intestinal injury, Paneth cells can acquire stem cell features to restore the intestinal epithelial integrity. In view of the crucial roles of Paneth cells in the intestinal homeostasis, research on Paneth cells has rapidly developed in recent years, and the existing reviews on Paneth cells have mainly focused on their functions of antimicrobial peptide secretion and intestinal stem cell support. This review aims to summarize the approaches to studying Paneth cells and introduce the whole life experience of Paneth cells from birth to death.